A Criminal Law Review on the Judge's Decision Regarding the Act of Persuading a Child to Engage in Sexual Intercourse (Study of Decision Number: 17/Pid.Sus-Anak/2025/PN.Tjk) - Akbar, Arizon Rahmanda; Prasetyawati, Endang; Ritonga, Rifandy (The Future of Education Journal, 2026)
The criminal act of persuading a child to engage in sexual intercourse constitutes a form of sexual violence against children that has serious impacts on their physical, psychological, and social development. Therefore, the handling of such cases must prioritize the principles of child protection and the best interest of the child, particularly within the juvenile criminal justice system. The application of criminal law provisions to children as offenders requires a balance between law enforcement and rehabilitative efforts. This principle is reflected in Decision Number 17/Pid.Sus-Anak/2025/PN.Tjk, which serves as the focus of this study. The issues examined in this research include the application of criminal law provisions to perpetrators who persuade children to engage in sexual intercourse and the judicial considerations underlying the sentencing of such perpetrators in Decision Number 17/Pid.Sus-Anak/2025/PN.Tjk. This study employs normative juridical and empirical research methods. The findings indicate that the application of criminal law provisions in Decision Number 17/Pid.Sus-Anak/2025/PN.Tjk is in accordance with Law Number 11 of 2012 on the Juvenile Criminal Justice System and Law Number 17 of 2016 on Child Protection. The elements of the criminal act of persuading a child to engage in sexual intercourse were proven legally and convincingly, leading the judge to appropriately apply Article 82 paragraph (1) in conjunction with Article 76E of the Child Protection Law. In imposing the sentence, the judge’s considerations emphasized not only legal certainty but also the principle of the best interest of the child through proportional, rehabilitative, and restorative sentencing, while still taking into account the protection of child victims and the future of the child offender.